Calycosin increases random-pattern skin flap survival by activating TFEB-mediated regulation of cell death - Ren-hao Jiang; Xuan-kuai Chen; Kang-yan Wang; Ke-jian Fu; Cheng-ji Dong; Zhu-liu Chen; Ying-ying Lai; Wei-yang Gao; An-yuan Wang (Journal of Functional Foods, 2024)
Random-pattern skin flaps play a vital role in repairing and reconstructing soft tissue defects. Clinical utilization of skin flaps is limited due to distal necrosis. Calycosin (CAL) is an effective ingredient present in Astragalus, and is reported to possess diverse pharmacological properties. Our study aims to assess the potential benefits of CAL on random flap survival and reveal the underlying mechanisms. Our study revealed that CAL promoted the survival area of the skin flap and improved flap blood flow. CAL treatment exerted anti-apoptosis and anti-ferroptosis effects in the flap model. In our mechanistic investigation, we demonstrated that CAL could activate the AMPK-mTOR signaling pathway and increase transcription factor EB (TFEB) nucleus translocation, thereby suppressing ferroptosis and apoptosis as a result of decreased reactive oxygen species (ROS) which was triggered by increasing superoxide dismutase 1(SOD1). In summary, our findings revealed CAL may protect against flap necrosis by inhibiting ferroptosis and apoptosis via AMPK-mTOR signaling pathway modulation.